Costs and cost-effectiveness of HIV early infant diagnosis in low- and middle-income countries: a scoping review - Elsbernd, Kira; Emmert-Fees, Karl M. F.; Erbe, Amanda; Ottobrino, Veronica; Kroidl, Arne; Bärnighausen, Till; Geisler, Benjamin P.; Kohler, Stefan (Infectious diseases of poverty, 2022)
Continuing progress in the global pediatric human immunodeficiency virus (HIV) response depends on timely identification and care of infants with HIV. As countries scale-out improvements to HIV early infant diagnosis (EID), economic evaluations are needed to inform program design and implementation. This scoping review aimed to summarize the available evidence and discuss practical implications of cost and cost-effectiveness analyses of HIV EID.